Sleep quality and job satisfaction in Spanish nurses: the consequences of COVID-19 - Maestro-González, Alba; Zuazua-Rico, David; Juan-García, Carmen; Villalgordo-García, Salvador; Mosteiro-Díaz, María Pilar; Plaza-Carmona, María (Revista Cuidarte, 2024)
Highlights• This study reveals that Spanish nurses have significantly poor sleep quality post-COVID-19, with a mean Pittsburgh Sleep Quality Index score of 9.75.• Factors such as not having dependents and having a master's degree were linked to poor sleep quality among the nurses surveyed.• Job satisfaction was the highest among female nurses and those not working with COVID-19 patients, indicating that sex and work conditions influenced satisfaction levels.• Improving nurse-to-patient ratios and shift distributions are crucial for enhancing sleep quality and reducing stress and burnout among nurses.Introduction: Sleep is fundamental to the quality of life and can affect individuals' well-being and mental health. Objective: This study analyzed sleep quality and job satisfaction among Spanish nurses following the COVID-19 pandemic. Materials and Methods: A cross-sectional study was conducted using the Pittsburgh Sleep Quality Index (PSQI), Font Roja Job Satisfaction Questionnaire, and sociodemographic and work-related variables. A “snowball” sampling method was employed through social media dissemination. Results: The mean PSQI score was 9.75 ± 4,36 points. The poorest sleep quality was identified in participants without dependents (p=0.031; β=3.329; 95% CI=0.035-6.354) and those with dependents other than children (p=0.022; β=4.121; 95% CI=0.575-7.667). However, having a Ph.D degree (p=0.001; β=-3.406; 95% CI=-5.503-1.309) or specialist degree (p=0.021; β=-1.639; 95% CI=-3.031- -0.247) was associated with better sleep quality. Higher job satisfaction was found among women (p=0.034; β=0.104; 95% CI=0.007-0.201) who did not work with COVID-19 patients (p=0.049; β=-0.085; 95% CI=-0.174- -0.003).   Discussion: Improving working conditions, such as the nurse-to-patient ratio and distribution of work shifts, is crucial to enhancing nurses' sleep quality. Conclusions:  Spanish nurses reported poor sleep quality. Not having dependents or having dependents other than children were risk factors for poor sleep quality. Job satisfaction was higher among women who did not work with COVID-19 patients. No relationship was found between job satisfaction and sleep quality.How to cite this article: Maestro-González Alba, Zuazua-Rico David, Juan-García Carmen, Villalgordo-García Salvador, Mosteiro-Díaz María Pilar, Plaza-Carmona María. Sleep quality and job satisfaction in Spanish nurses: the consequences of COVID-19. Revista Cuidarte. 2024;15(2):e3452.  https://doi.org/10.15649/cuidarte.3452
Keywords: COVID-19; Sleep; Sleep Hygiene; Job Satisfaction; Nursing